A Study on knowledge, attitude and use of hormonal contraceptives among University students - (:unkn) unknown (My University, 2015)
There has been sustained campaign for adoption of hormonal contraceptives for use by the general population worldwide to avoid unwanted pregnancies, unsafe abortions and reduce population growth. The main targets of these campaigns are the teenagers in schools, both primary and secondary since they are the most risk of unwanted pregnancies.
9TH Annual ethics conference. Theme : Bioethics medical, legal, environmental and cultural aspects in healthcare ethics at STRATHMORE UNIVERSITY, 25-26 OCTOBER 2012.
Keywords: Hormonal contraceptives